Complication of tunneled dialysis catheter of chronic ulcer in the site of vascular access entry leading to suspected squamous cell carcinoma (SCC): a case report - Febriana Rizky Ramadhani; A Herdianti; RE Intan; AN Sabrina; GS Putro; E Septira (Journal of Indonesia Vascular Access, 2022)
Introduction: Catheter-related infection (CRI) is one of the most common vascular access complications in dialysis catheter-related procedures. However, repeated chronic infected ulcer that leads to suspected malignancy in a tunneled dialysis catheter (TDC) insertion site and its risk factor have not been reported. Case description: A 37 years-old woman presented with a chronic exudative ulcer in the right breast at the entry site of a tunneled dialysis catheter. The past medical history included type 2 diabetes mellitus, chronic kidney disease, hepatitis C, and obesity. The patient had routine hemodialysis with TDC for the last 2 years and had changed the TDC access 3 times due to recurrent CRI. At first, the lesion appeared as a small pustule and enlarged recurrently. Later, the lesion progressed into an 82x80 mm raised crateriform exudative ulcer with a raw surface similar to Marjolin’s ulcer squamous cell carcinoma. The patient was referred to oncology due to limited facilities in our hospital. Conclusion: CRI is one of the most common long-term complications of TDC. In out of the case, this led to chronic infection and change in TDC, chronic inflammation then became Marjolin’s Ulcer. Risk factors for suspected SCC in our patient were immunosuppressive state from diabetes, hepatitis C, CKD, and chronic inflammation from a repeated chronic infected ulcer. SCC can be considered a long-term complication of TDC. Early prevention of CRI and risk factor controlling should be considered to prevent such complications.